Implementasi Penguatan Profil Pelajar Pancasila Melalui Kegiatan Ko-Kurikuler Di SMA Negeri 1 Gedeg - Haq, Zilda Brilliani Arina Sabilla; Rohmad, Ali; Saifuddin (PT. Kreasi Karya Majakata, 2024)
This study aims to determine and analyze the effect of promotion and service quality on The Pancasila Student Profile is a concept promoted by the Indonesian Ministry of Education and Culture in order to shape student character in accordance with Pancasila values. This profile is expected to be a guide in the educational learning process to build a superior and integrated generation, by going through several stages that both the government and school policies have designed. This study aims to analyze the implementation of the Pancasila Student Profile through co-curricular activities at SMA Negeri 1 Gedeg, the role of teachers and also what are the supporting and inhibiting factors of the Pancasila student profile. This study uses a qualitative descriptive approach, the data of which are obtained through observation, interviews, and documentation. The results of the study indicate that the implementation of this co-curricular activity is an integral part of the Merdeka Curriculum, which focuses on developing student character in accordance with Pancasila values such as traditional dance, entrepreneurship, and video making, effective in internalizing Pancasila values in students and able to achieve the goal of having a Pancasila Student Profile as a whole. In the implementation of P5, the influence of the teacher's role is very important during the sustainability of P5, such as understanding, preparation, approach, and mentoring. The Pancasila Student Profile has the main supporting factors, namely adequate facilities and infrastructure and full support from the school and teachers. However, there are several inhibiting factors, such as limited resources and varying student participation. This implementation forms not only superior academics but also a young generation that is responsible, cultured and has a strong character in accordance with the values of Pancasila. Thus, co-curricular activities at SMA Negeri 1 Gedeg have succeeded in strengthening the character of the nation through holistic and sustainable education.